Transformative pastoral leadership in the Black church - Tribble, Jeffery L., Sr (Palgrave Macmillan, 2005)
Transformative Pastoral Leadership in the Black Church offers practical wisdom from comparative analysis of the experiences of a male pastor and a female pastor in the Christian Methodist Episcopal Church. Church leaders must be transformed themselves as they are transforming their churches to serve their communities. From his research of the perspectives of laity, clergy, and scholars of the black church, Jeffery L. Tribble offers hopeful stories and helpful strategies for those who believe that the black church must continue its historic mission of being an instrument of survival, elevation, and liberation for its people. Transformative Pastoral Leadership in the Black Church is an important contribution to studies of black religion, womanist thought, and social justice.